Die Freimaurer im Alten Preußen 1738-1806, Die Logen in Berlin Die Logen in Berlin - Gerlach, Karlheinz (Studien Verlag, 2014)
"The Lodges in Berlin" is the first part of the trilogy "The Freemasons in Old Prussia" (p.2 " The Lodges between the Middle Oder and the Lower Rhine", and p.3 "The Lodges in Pomerania, Prussia and Silesia", published in Innsbruck in 2007 and 2009 resp.). The Research based on the preserved data of the archives (Geheimes Staatsarchiv Preußischer Kulturbesitz, Berlin), on the masonic literature as well as on the literature about Prussia. The Focus lies on the 27 Berlin lodges with their entire Membership (§880 members) as well as their social structure as part of the cultural history of Prussia and the General history of Freemasonary.